2015
DOI: 10.1177/0022343315610399
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of low-intensity intergroup violence

Abstract: What accounts for low-intensity intergroup violence? This article explores the determinants of low-intensity sectarian violence in Northern Ireland, which has marked the post-1998 peace agreement period. Low-intensity violence comprises a variety of events from riots to attacks against other civilians as well as against homes and symbolic buildings such as churches. We argue that this violence is more likely and prevalent in interface areas where similarly sized rival communities are geographically in contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…warned of the dangers of power-sharing (Rothchild & Roeder, 2005) or of cohabitation between equally dominant ethnic or religious groups (Balcells, Daniels & Escribà-Folch, 2016), and have suggested that violence often accompanies minority access to political power (Dancygier, 2010). Our results are more consistent with these latter intuitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…warned of the dangers of power-sharing (Rothchild & Roeder, 2005) or of cohabitation between equally dominant ethnic or religious groups (Balcells, Daniels & Escribà-Folch, 2016), and have suggested that violence often accompanies minority access to political power (Dancygier, 2010). Our results are more consistent with these latter intuitions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to predict national-level conflicts -for example, civil war, political instability (Goldstone et al, 2010) or 'irregular regime change' (Beger, Dorff & Ward, 2016). 1 Recently, however, the most active frontier of conflict research has focused on local-level incidents, including murders (Blakeslee & Fishman, 2015), riots (Wischnath & Buhaug, 2014), domestic violence (Sekhri & Storeygard, 2013), 'lowintensity' sectarian clashes (Balcells, Daniels & Escribà-Folch, 2016), conflicts between states and underrepresented groups (Cederman, Wimmer & Min, 2010), and killings of suspected witches (Miguel, 2005). Like its cross-national counterpart, most subnational conflict research has been descriptive or causal.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ethnic groups that constitute a larger proportion of the national population, but are excluded from the national political system, are more likely to perceive themselves as being unfairly treated and will have a larger potential resource pool from which to recruit Buhaug 2013, Cederman, Wimmer, andMin 2010). Groups who approach demographic parity with each other and who perceive themselves to be under threat, are found to be more likely involved in intergroup violence with each other, because both groups are able to compete for dominance (Balcells, Daniels, and Escribà-Folch. 2016):…”
Section: Moderators Of the Effect Of Political Discriminationmentioning
confidence: 99%
“…Clustering itself can also endanger refugees or IDPs (Steele, 2018). However, there may also be a level at which violence associated with segregation reaches a plateau, as Balcells, Daniels & Escribà-Folch (2016) found with Northern Ireland, and Weidmann & Salehyan (2013) in Iraq.…”
Section: The Potential Implications Of Resettlement Patterns For Violmentioning
confidence: 99%